AN INVESTIGATION OF STUDENTS’ PERCEPTIONS OF ORAL CORRECTIVE FEEDBACK IN EFL PUBLIC SPEAKING COURSE - M. Alpian Sari; M. Zaini Miftah; Hesty Widiastuty (PROJECT (Professional Journal of English Education), 2022)
This study was aimed at the investigation to know-how are the students' perceptions about oral corrective feedback given by the teacher in the EFL Public Speaking course. This study was mixed method. The research sample of this study was the 5th-semester students of the public speaking course in the academic year 2020/2021 of IAIN Palangka Raya. Questionnaire and interview were used as the instruments. The data were analyzed using SPSS and Microsoft Excel software. The result showed that: (1) Students feel oral corrective feedback is necessary and helpful in the public speaking course and they are learned a lot from oral corrective feedback because there were 25 students who chose to answer Agree (72%) and Strongly Agree (20%). (2) Students accept all kinds of oral corrective feedback by the teacher because 52-76% of students agree to all kinds of oral corrective feedback. (3) Students prefer all ways to deliver oral corrective feedback because 52-72% of students agree to all methods to delivering oral corrective feedback. (4) Students feel motivated, comfortable, and being happy by oral corrective feedback because 88% of students agree that they feel motivated and 80% of students feel happy and comfortable by oral corrective feedback. Keywords:  Students Perception, Oral Corrective Feedback, EFL Students, Public Speaking Course